Harmonizing Culture and Religious Traditions in Multi-Religious Families - Hawa, Hawa' Hidayatul Hikmiyah; Wagianto, Ramdan; Syafi’i, Imam; Nugroho, Irzak Yuliardy; Ihsani, A. Fikri Amiruddin (Santara: Journal of Islamic Law and Humanity, 2025)
Conception and harmonization of religious culture and traditions within multifaith families in three villages known as centers of religious moderation in Malang City. The background to this study arises from the complexity of urban life characterized by religious and cultural diversity, which demands harmonious management of differences within the family and community context. This research uses a qualitative approach with a case study method, involving in-depth interviews, participant observation, and analysis of local documents as the primary data sources. The results show that multifaith families in the three villages are able to build harmony through several strategies: mutual respect for each member's religious practices, adapting traditions and rituals to be inclusive, and maintaining open communication between family members and neighbors. Furthermore, social interactions at the village level, such as joint celebrations, community activities, and support among residents, contribute to strengthening social cohesion and fostering values of tolerance. This research confirms that the harmonization of religious culture and traditions is not merely a normative concept, but a practice that can be realized through awareness, flexibility, and appreciation of differences. These findings contribute to the understanding of religious moderation at the local level and serve as a reference for developing an adaptive and harmonious model for managing multifaith family diversity.